2016
DOI: 10.3109/0886022x.2016.1160248
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological responses of the Swiss albino mice treated with uranyl nitrate and its recovery

Abstract: Uranium is a radioactive heavy metal ubiquitous in the natural environment. In its chemical form, it is known to induce nephrotoxicity both in human and in animals. Its toxicity is dose and time dependent, also varies with form of uranium. In the present study, we assessed the nephrotoxicity induced by a single dose of uranyl nitrate (UN) in mice at different time intervals and recovery from its toxicity. Two doses of 2 and 4 mg/kg body weight of uranyl nitrate was injected intraperitoneally and animals were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…These assessments were qualitative, however, and did not provide measurements of uranium content. Other studies have reported tubular damage involving both the cortex and medulla of kidneys in mice injected with uranyl nitrate [ 8 ] or uranyl acetate [ 6 ] or in rats implanted with depleted uranium [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These assessments were qualitative, however, and did not provide measurements of uranium content. Other studies have reported tubular damage involving both the cortex and medulla of kidneys in mice injected with uranyl nitrate [ 8 ] or uranyl acetate [ 6 ] or in rats implanted with depleted uranium [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rats and mice exposed to uranium compounds by injection, inhalation or through drinking water, show signs of nephrotoxicity [ 4 ]. Studies of histological changes indicate the most damage in the corticomedullary region containing the pars recta segment of the nephron [ 5 8 ]. Previous analyses of uranium toxicity in the kidney are limited, however, by the lack of quantitative measurements of this element in different regions of the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Collected urines are used to quantify uranium or fluoride, to measure specific and sensitive biomarkers of nephrotoxicity levels and to assess clinical bioassays. Finally, animals are euthanized 48h and 72h after exposure, chosen as the peak of nephrotoxicity is observed after intraperitoneal injection [3]. The protocol is shown in figure 1.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Indeed, acute exposure to U induces nephrotoxicity in both humans and animals [6,14] and this impairment is mainly observed in proximal tubule renal epithelial cells [15,16]. After acute exposure of 1 to 5 mg/kg U injected intraperitoneally or intramuscularly, rodents demonstrated tubular necrosis and changes in blood chemistry reflecting severe renal alterations [16,17,18]. Similarly, intravenous acute exposures to F induce kidney damage in rats [19], even at low concentrations [20].…”
Section: Introductionmentioning
confidence: 99%